Haiti : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2015)
This Selected Issues paper examines opportunities and challenges for growth in Haiti. Achieving a sustained increase in living standards in Haiti will require deep-seated reforms across a range of areas. Diversifying the export base is needed to cushion the impact of severe shocks that have reduced per capita income and prevented a sustained increase in the capital stock. Integration into global-value chains would also allow Haiti to take advantage of its proximity to the U.S. market and favorable trade preferences to generate employment, spur the creation of human capital, and allow Haiti to begin climbing the value added chain.